Effect of finite beta on neoclassical transport characteristics in CFQS quasi-axisymmetric stellarator - Yang Lang; Mitsutaka Isobe; Akihiro Shimizu; Hiroyuki Yamaguchi; Kunihiro Ogawa; Haifeng Liu; Yuhong Xu (Journal of Physics Communications)
CFQS is the world’s first modular-coil-type quasi-axisymmetric stellarator, which is currently under construction. This study systematically investigates the effect of finite beta (volume-averaged beta, 〈 β 〉) on the neoclassical transport characteristics of CFQS plasmas. An intensification of the finite- β effect increases the neoclassical bootstrap current and amplifies variations in the major helical ripple component B _1,1 and other non-axisymmetric magnetic components. During this process, the magnetic flux surfaces essentially remain at moderate β values (〈 β 〉 = 0.77%); however, at high β values (〈 β 〉 = 2.03%), the flux surface becomes significantly deformed due to intensified axisymmetry breaking. The neoclassical diffusion properties in the CFQS are investigated for different finite β values using the independently developed Monte Carlo Neoclassical Transport Simulation code. The charged-particle fluxes are estimated as functions of the radial electric field. Subsequently, the neoclassical diffusion coefficients and plasma parameters at moderate β (〈 β 〉 = 0.77%) and high β (〈 β 〉 = 2.03%) values are examined under ambipolar conditions. Electron roots are observed to provide strong confinement in the CFQS at various finite β values.